2009
DOI: 10.1074/jbc.m109.020495
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Stat3 by Activating PTPN11 Mutants Contributes to the Pathogenesis of Noonan Syndrome and Juvenile Myelomonocytic Leukemia

Abstract: Noonan syndrome (NS) is an autosomal dominant congenital disorder characterized by multiple birth defects including heart defects and myeloproliferative disease (MPD). Approximately 50% of NS patients have germline gain-of-function mutations in PTPN11, which encodes the protein-tyrosine phosphatase, Shp2. We provide evidence that conditional ablation of Stat3 in hematopoietic cells and cardiac valvular tissues leads to myeloid progenitor hyperplasia and pulmonary stenosis due to the leaflet thickening, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 49 publications
2
41
2
Order By: Relevance
“…On the other hand, AS was observed frequently in Sos1 EK/EK mice and in older Sos1 +/EK mice. Finally, in addition to activation of Ras and Erk, we found that Rac and Stat3 were also activated in Sos1 EK mice, which was not found in the Ptpn11 models (38)(39)(40)44). It is possible, if not likely, that the common phenotypes observed in Sos1 and Ptpn11 models, such as growth delay, craniofacial features, hematological disorders, and some cardiac defects, were due to the enhanced Erk activation seen in both models, whereas the distinct features in the Sos1 model described above were due to the selective activation of Rac and/or Stat3.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, AS was observed frequently in Sos1 EK/EK mice and in older Sos1 +/EK mice. Finally, in addition to activation of Ras and Erk, we found that Rac and Stat3 were also activated in Sos1 EK mice, which was not found in the Ptpn11 models (38)(39)(40)44). It is possible, if not likely, that the common phenotypes observed in Sos1 and Ptpn11 models, such as growth delay, craniofacial features, hematological disorders, and some cardiac defects, were due to the enhanced Erk activation seen in both models, whereas the distinct features in the Sos1 model described above were due to the selective activation of Rac and/or Stat3.…”
Section: Discussionmentioning
confidence: 64%
“…4E). Because STAT3 is a substrate of SHP2 (33, 34), the diminished STAT3 activity was likely caused by enhanced dephosphorylation of STAT3 by hyperactive SHP2 E76K .…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the activity of Stat3, one of the known substrates of Shp2 phosphatase (37,38) that has been shown to play an essential role in the mitochondria (39). We found that phosphorylation levels of tyrosine 705 of Stat3, the target of Shp2 enzymatic activity, were substantially decreased in the cytosol and mitochondria of Ptpn11 E76K/Ï© cells (Fig.…”
Section: Lytic Capacity In Ptpn11mentioning
confidence: 99%